Bridging the digital divide to enhance teaching and learning for human capital development in the East Coast Economic Region (ECER) of Malaysia - Abdulai, Abdul-Mumin; Siwar, Chamhuri; Ismail,, Abdul Ghafar; Mohd Noor, Noor Azlan; Makol-Abdul, Pute Rahimah (2012)
This paper has examined the extent to which addressing the issue of digital divide can enhance teaching and learning in order to produce the human capital required to support the development agenda of the east coast economic region (ECER). This region consists of three relatively lessdeveloped states and a district in Malaysia (i.e., Kelantan, Pahang, Terengganu, and Mersing District). Inadequate human capital, especially skilled labour, has been identified as one of the major factors underpinning ECER’s underdevelopment. Although Malaysia happens to be one of the few Southeast Asian countries with medium to high internet penetration, the fact that the regions and states differ in terms of the available resources, social and public infrastructure underscores the likelihood of unequal access to digital technology among them. Making digital technology readily available and accessible in the ECER may facilitate the training of the right calibre of manpower. It is argued that developing human capital is possible only through strong and efficient educational system (Chamhuri, 2005; Abdulai and Chamhuri, 2008, p. 7). And the use of digital technology that includes, of course, information and communications technology in the teaching and learning process has tremendously enhanced educational system in the majority of countries, particularly in research and development endeavours. It is the belief of the authors that the Malaysian Government will not be oblivious of the crucial benefits associated with tackling the digital divide issue in the ECER. In that light, what measures does the Government put in place to tackle this issue? And how effective are such measures? Addressing these questions constitutes the main objective of the paper.